Prestasi Akademik: Pengaruh Minat Siswa Dan Kecerdasan Emosional Dalam Pembelajaran Bahasa Inggris - Ariani, Farida; Reflianto, Reflianto; Wandi, Joni Indra; Afnita, Nora (Ikhtisar: Jurnal Pengetahuan Islam, 2023)
To create a more enjoyable English language learning environment for students, an emotional approach is often required. This is because learning English is sometimes perceived as intimidating by some students. The purpose of this research is to evaluate the influence of students' interest and emotional intelligence on their learning outcomes. The research method employed is quantitative research with a survey approach adopting a cross-sectional design. The research sample consists of 40 seventh-grade students at SMP Negeri 1 Pariaman, selected using purposive random sampling. Research instruments include observation sheets, questionnaires, and documentation. The data analysis results indicate that students' interest and emotional intelligence significantly affect their learning outcomes. Therefore, it is recommended for English teachers to pay more attention to students' interests and emotional intelligence in their efforts to enhance understanding and academic achievements.